Gray glass with low light transmittance

By using colorants composed of metal oxides such as Fe2O3, FeO, Co3O4, Se, CuO and TiO2, combined with the float process, the problems of high cost of gray glass and nickel sulfide inclusions in the prior art are solved, and low-cost and excellent Preparation of grey glass with sunlight control performance.

CN119263633APending Publication Date: 2025-01-07VITRO FLAT GLASS LLC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410897061.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2024-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing gray glass compositions for the automotive industry are costly due to the need to use rare earth oxides, and there is a problem that the glass sheet may be broken by the nickel sulfide inclusions.

Method used

Using colorants composed of metal oxides such as Fe2O3, FeO, Co3O4, Se, CuO and TiO2, by controlling the redox ratio and process conditions, gray glass with low light transmittance and excellent sunlight control performance is produced to avoid using Expensive nickel, chromium, manganese or rare earth element oxides and form glass by float process.

Benefits of technology

Low-cost and low-transmittance grey glass preparation is achieved, avoiding the formation of nickel sulfide inclusions, and meeting the automotive industry's demand for optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

Gray glass having low light transmittance. The gray glass with low light transmittance formed from the composition includes a colorant. The colorant includes from 1.8 wt% to 2.3 wt% of Fe2O3, from 0.28 wt% to 1.2 wt% of FeO, from 0.030 wt% to 0.040 wt% of Co3O4, from 0.0020 wt% to 0.010 wt% of Se, from 0.00050 wt% to 0.050 wt% of CuO, and from 0.01 wt% to 1 wt% of TiO2. The glass has a visible light transmission (TLA) of less than 15%, a direct solar transmission (TDS) of less than 14%, an infrared radiation transmission (TIR) of less than 14%, an ultraviolet light transmission (TUV) of less than 8%, and a total solar transmission (TTS) of less than 38%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates generally to neutral gray, low transmittance glass, and more particularly, to compositions of gray glass for use in the automotive industry, such as panoramic roofs and rear door side windows. Background Art

[0002] Tinted glass is a material into which metal oxides are doped during the melting process. It is common to add iron-cobalt oxide in combination with selenium so as to produce a glass shade ranging from light green or neutral gray to yellow-gray according to the ratio of the additives. By controlling the concentration of iron oxide, cobalt oxide and selenium and controlling the redox conditions (mainly the concentration of carbon and sodium nitrate) in the glass melting atmosphere and / or the mixture, it is possible to produce glass with low light transmittance, desired blocking of direct sunlight, and privacy gray tinting, which can be used in automotive applications for panoramic roofs and rear doors of motor vehicles. The disadvantages of the glass compositions currently used include the high cost caused by the need to use rare earth oxides in order to achieve the desired material properties and optical properties.

[0003] Therefore, those skilled in the art continue to conduct research and development in the field of gray glass for the automotive industry. Summary of the invention

[0004] Disclosed is a gray glass having low light transmittance formed from a composition.

[0005] In one example, the gray glass with low light transmittance has a composition including a colorant. The colorant includes: 1.8 wt% to 2.3 wt% Fe2O3; 0.28 wt% to 1.2 wt% FeO; 0.030 wt% to 0.040 wt% Co3O4; 0.0020 wt% to 0.010 wt% Se; 0.00050 wt% to 0.050 wt% CuO; 0.01 wt% to 1 wt% TiO2; and a redox ratio of 15 to 40% (based on the total weight of the glass). The glass has a visible light transmittance (T LA ), less than or equal to 14% direct sunlight transmittance (T DS )(di rectsolar transmi t tance), infrared radiation transmittance less than or equal to 14% (T IR ), less than or equal to 8% UV transmittance (T UV ) and a total solar energy transmittance (T TS ).

[0006] In one example, the gray glass with low light transmittance is formed from a composition including: 68 wt% to 75 wt% SiO2; 0 wt% to 5 wt% Al2O3; 5 wt% to 15 wt% CaO; 0 wt% to 10 wt% MgO; 10 wt% to 18 wt% Na2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3; and a colorant comprising: 1.8 wt% to 2.3 wt% Fe2O3; 0.28 wt% to 1.2 wt% FeO; 0.030 wt% to 0.040 wt% Co3O4; 0.0020 wt% to 0.010 wt% Se; 0.00050 wt% to 0.050 wt% CuO; 0.01 wt% to 1 wt% TiO2; and a redox ratio of 15 to 40%. In another example, the glass has a visible light transmittance (T LA ), less than or equal to 14% direct sunlight transmittance (T DS ), less than or equal to 14% infrared radiation transmittance (T IR ), less than or equal to 8% UV transmittance (T UV ) and a total solar energy transmittance (T TS )(tota l solar transmi ttance).

[0007] Also disclosed is a method for manufacturing gray glass with low light transmittance using a conventional float non-vacuum glass system.

[0008] In one example, the method includes: melting a glass batch to provide a pool of molten glass; flowing the pool of molten glass onto a molten tin bath; moving the molten glass over a surface of the molten tin bath while controllably cooling the molten glass and applying forces to the molten glass to provide glass of a desired thickness; and removing the glass from the molten tin bath; wherein the glass comprises: 68 wt % to 75 wt % SiO2; 0 wt % to 5 wt % Al2O3; 5 wt % to 15 wt % CaO; 0 wt % to 10 wt % MgO; 10 wt % to 18 wt % Na 2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3; and a colorant, the colorant comprising: 1.8 wt% to 2.3 wt% Fe2O3; 0.28 wt% to 1.2 wt% FeO; 0.030 wt% to 0.040 wt% Co3O4; 0.0020 wt% to 0.010 wt% Se; 0.00050 wt% to 0.050 wt% CuO; 0.01 wt% to 1 wt% TiO2; and a redox ratio of 15 to 40%. In another example, the glass has a visible light transmittance (T LA ), less than or equal to 14% direct sunlight transmittance (T DS ), less than or equal to 14% infrared radiation transmittance (T IR ), less than or equal to 8% UV transmittance (T UV ) and a total solar energy transmittance (T TS ).

[0009] Other examples will become apparent from the detailed description that follows. DETAILED DESCRIPTION

[0010] As used herein, all numbers used in the specification and claims to represent dimensions, physical properties, processing parameters, ingredient amounts, reaction conditions, etc. should be understood to be modified by the term "approximately" or "about" in all cases. Therefore, unless otherwise indicated, the numerical values ​​listed in the following specification and claims can vary according to the desired properties attempted to be obtained by the present disclosure. At least, and without intending to limit the application of the doctrine of equivalents to the scope of the claims, each numerical value should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques. In addition, it should be understood that all ranges disclosed herein cover range starting values ​​and range ending values ​​and any and all sub-ranges contained therein. For example, the range of "1 to 10" should be considered to include any and all sub-ranges between the minimum value 1 and the maximum value 10 (including the minimum and maximum values); that is, all sub-ranges starting with a minimum value of 1 or greater and ending with a maximum value of 10 or less, such as 1 to 3.3, 4.7 to 7.5, 5.5 to 10, etc. "A" or "an" refers to one or more.

[0011] As used herein, the phrase "at least one of," when used with a list of items, means that different combinations of one or more of the listed items may be used, and only one of each item in the list may be required. For example, "at least one of item A, item B, and item C" may include, but is not limited to, item A or item A and item B. This example may also include item A, item B, and item C, or item B and item C. In other examples, "at least one of" may be, for example, but not limited to, two of item A, one of item B, and ten of item C; four of item B and seven of item C; and other suitable combinations.

[0012] The present disclosure relates to compositions and methods for making tinted glass. Tinted glass is a material into which metal oxides are incorporated during the melting process. As a result of previous studies, it is known that the combined addition of iron-cobalt oxides with selenium imparts a glass chromaticity ranging from light green or neutral gray to yellow-gray, depending on their ratio. By controlling the concentrations of iron oxides, cobalt oxides, and selenium and controlling the redox conditions in the glass melting atmosphere and / or the mixture (primarily the concentrations of carbon and sodium nitrate), it is possible to produce glass with low light transmittance, desired blocking of direct sunlight transmission, and privacy gray tinting, which can be used in automotive applications for panoramic roofs and rear doors of motor vehicles.

[0013] The glass described in the following examples refers to a type of neutral grey glass based on three main colorants: iron oxide, cobalt oxide and selenium, whose main function is to provide solar control properties to the glass.

[0014] The following patents and publications provide examples of using various metal oxides as primary colorants to obtain gray glass and provide the final characteristics of the product. These components, such as nickel oxide, manganese oxide, chromium oxide or rare earth oxides, are mixed into the basic formula of silica-soda-calcium glass.

[0015] For example, Combes et al., U.S. Pat. No. 5,352,640 (U.S. Pat. No. RE37,998E) discloses obtaining a gray glass mainly for the automotive industry, the composition range of the colorant is 1.4% to 4% total iron and 0% to 0.05% cobalt oxide, with excess iron oxide, when Fe2O3 is less than 2%, cobalt is about 0.02%, and optionally, it can have a combination of CoO+Se+Cr2O3 with a content of less than 0.24% by weight. The physical properties of the glass, such as light transmittance and energy transmittance, are equal to or less than 20% under illuminant A and equal to and less than 12% at a thickness of 3.85 mm, respectively.

[0016] In U.S. Pat. No. 5,545,596 to Alvarez Casar iego et al., it is disclosed that the following concentrations of dyes are used: total iron concentration is 0.45 to 2.5%, CoO concentration is 0.001 to 0.02%, Se concentration is 0 to 0.0025%, Cr2O3 concentration is 0 to 0.1%, and gray glass with a light transmittance of 20 to 60% for the illuminant A in the vehicle side windows and rear windows is used.

[0017] US Patent No. 7,393,802 B2 to Seto et al. discloses the use of Fe2O3, CoO, Se and NiO as colorants, but also adds the use of CeO2 and TiO2 in an amount of not more than 2.0 wt. % to increase UV absorption.

[0018] For the glasses obtained in US Pat. No. 7,622,410 assigned to Longobardo et al., in addition to a total content of iron oxides of 0.15 to 0.45%, less than or equal to 3 ppm of selenium and 120 to 240 ppm of cobalt oxide, nickel oxides in a concentration of 500 to 1000 ppm, erbium oxide (Er2O3) in a concentration of 0.1 to 0.8%, chromium oxides in a content of 1 to 20 ppm are used. The mixture of these oxides is used for the general adjustment of the gray coloring of the glass. The glasses of this patent have a light transmittance of 8 to 25%, a dominant wavelength of 435 to 570 nm, using a cobalt oxide / nickel oxide ratio of 0.22 to 0.30 and a redox value of FeO / Fe2O3 of 0.20 to 0.40. A significant disadvantage of these disclosed glasses is the high cost of the rare earth oxides required in their composition.

[0019] In US Pat. No. 8,017,538 B2 to Teyssedre et al., it is known that a glass is proposed using nickel oxide in a concentration of 400 to 700 ppm or 1500 to 1900 ppm, iron oxide 0.7 to 0.95% with a redox value of 0.40 or less, in addition to 200 to 300 ppm of cobalt oxide, to obtain a gray adjustment and to obtain the following physical properties: a light transmittance under illuminant A (TLA) of 50% or less, and an average value of energy transmittance (TE) of less than 45% for a glass thickness of 3.85 mm. The use of nickel oxide used as a colorant in some of the aforementioned patents has the following disadvantages: nickel sulfide inclusions (a defect that is not easily detectable) may be formed, which can cause the glass sheet to break due to the difference in the thermal expansion coefficient of this material and the rest of the glass matrix. The glasses described in U.S. Pat. No. 8,551,899 to Kim et al. have a dark neutral gray-green coloration due to the dyes used, such as 1.4 to 2.5% Fe2O3, 0.02 to 0.04% CoO, 0.0001 to 0.004% Se, 0.005 to 0.5% MnO and 0.05 to 1% CeO, and have a light transmission of less than 15% illuminant A. These glasses are used as privacy glass or panoramic sunroofs in automobiles, and in buildings.

[0020] U.S. Patent No. 7,754,632 to Delmotte et al. uses a MnO concentration of up to 600 ppm and a TiO2 concentration of less than 0.1%, in addition to other oxides such as 1.1 to 1.5% Fe2O3 (total iron), 150 to 200 ppm Co, 25 to 100 ppm Cr2O3 and 10 to 50 ppm Se, in order to achieve an optical property of a light transmittance of less than 20% for the illuminant A for a thickness of 4 mm.

[0021] Tsuzuki et al., U.S. Pat. No. 8,785,338, mentions a silica-soda-lime glass composition having the following contents: 0.70 to 1.70 mass % Fe2O3 (total iron), 0.15 to 0.45 mass % FeO (ferrous oxide), 0-0.8 mass % TiO2, 100 to 350 ppm CoO, 0 to 60 ppm Se, 100 to 700 ppm Cr2O3, and 3 to 150 ppm MnO, having a ferrous ion to ferric ion ratio (Fe2O3) of 0.20 to 0.80. 2+ / Fai th 3+ ). The patent discloses that, in addition to sufficient transparency, the glass also has excellent ultraviolet radiation absorption properties and infrared radiation absorption properties (thermal insulation properties), which is achieved by using TiO2 preferably in the range of 0 to 0.5%.

[0022] Lee et al., U.S. Pat. No. 9,120,695, discloses the following glass composition: 1.4 to 2% Fe2O3, wherein the FeO content is 10 to 30% (relative to total iron), 0.02 to 0.035% CoO, 0.0015 to 0.004% Se, and 0.005 to 0.5% MnO. The following optical properties are reported: less than 15% illuminant A light transmittance and less than 2% UV transmittance.

[0023] The dark green glass disclosed in U.S. Pat. No. 9,617,182 (April 11, 2017) by Cho et al. discloses 1.2 to 2% total Fe2O3 as a dye, 0.0220 to 0.04% CoO, 0.002 to 0.0035% Se and 0.01 to 0.04% Cr2O3, wherein the weight ratio of (CoO+Cr2O3) to Se (=[CoO+Cr2O3] / Se) is 13 to 25, and the weight ratio of CoO to Cr2O3 (=CoO / Cr2O3) is 0.9 to 1.8. The glass exhibits a visible light transmittance (T LA ), 16% or less direct solar transmittance (T DS ), and a transmittance of 3% or less of ultraviolet radiation (T UV ), measured against a 4 mm thickness benchmark.

[0024] US Patent No. 7,902,097 B2 by Cid-Aguilar et al. uses the following concentrations: 0 to 30 ppm Co3O4, 1 to 20 ppm Se, 20 to 200 ppm CuO and 0.30 to 0.70% Fe2O3 to obtain a glass of neutral gray color with the following optical characteristics: light transmittance with illuminant A greater than 65%, total solar transmittance equal to or less than 60%, transmittance of ultraviolet radiation less than 46%, dominant wavelength 490 to 600 nm. The patent discloses the addition of components such as 0.01 to 0.07% carbon or 0.2 to 1.2% sodium nitrate to change the oxidation-reduction state of the oxides of iron and copper, as it can be used as an alternative to obtain gray tones in combination with other dyes, partially replacing the addition of titanium oxide and cobalt oxide.

[0025] According to the above disclosure, iron is present in the glass (silicon-sodium-calcium) in two compounds, depending on the oxidation state of the iron: if the iron is in the form of Fe 2+ If iron exists in the form of Fe 3+In the form of ferrous iron, the compound formed is iron oxide (Fe2O3). Each ion imparts different properties; ferrous ions have a wide and strong absorption band centered at 1050nm, which leads to a reduction in infrared radiation. In addition, this band extends into the visible region, thereby reducing light transmittance and imparting a light blue color to the glass. On the other hand, ferric ions present a strong absorption band in the ultraviolet region, which prevents them from transmitting through the glass, and in addition, they have two other weak bands in the visible region between 420 and 440nm, which can cause a slight reduction in light transmittance and yellowing in the glass. Typically, the amount of iron and its ferrous oxide in glass is expressed in the form of Fe2O3. The amount of ferrous oxide or ferric oxide is usually expressed as a percentage of the total iron. The balance between ferrous oxide and ferric oxide has a direct impact on the color and transmittance characteristics of the glass and can be expressed as:

[0026] Iron ions (Fe 3+ ) amount, the greater the absorption of ultraviolet radiation and the light transmittance will increase, as well as the yellowish hue. 2+ ) content increases, the absorption of infrared radiation will increase, but the absorption of ultraviolet radiation will decrease, and the light transmittance will also decrease.

[0027]

[0028]

[0029] The change in FeO concentration relative to Fe2O3 causes color changes in the glass. The hue shift can change from yellow through green, blue to amber. The color changes are as follows (based on experimental results): Yellow - low ferrous iron (12%) - high transmittance (high ferric ions) yellow-green (16%). Green - yellow (20%) green (25% typical green glass); teal green (29%); green-blue (35%); blue (50%); olive green (60%) champagne (65%); and amber - high ferrous iron (75%) - low transmittance (low ferric ions).

[0030] In order to control the balance between ferrous oxide and ferric oxide required to achieve solar control glass, it is beneficial to establish the conditions in the mixture and in the melting atmosphere. On the one hand, the concentrations of reducing agents such as carbon and oxidizing agents such as sodium sulfate and sodium nitrate can be selectively adjusted. In terms of melting conditions, it may be beneficial to adjust an atmosphere with more or less oxygen content, depending on the thermal properties and the desired glass color.

[0031] Additionally, it is well known that titanium oxide also acts as a colorant and when used in combination with Fe2O3, further reductions in UV transmittance can be obtained until a point is reached where the desired visibility transmission is achieved.

[0032] In the paper Modern Automotive Glasses, Glass Technology, vol 37, February, 1996, pp. 2-6, KM Fules discloses that iron is the most important colorant in automotive glass because it is a cheaply available component that absorbs undesirable ultraviolet radiation (ferric ions) and also absorbs a large amount of infrared radiation (ferrous ions).

[0033] In the article "The color of iron-containing glasses of varying composition", Journal of the Society of Glass Technology, New York, USA, April, 1950, pp. 332-406, Gordon F. Bres term et al. disclosed the color changes caused by systematically varying the composition of iron-containing silicate and non-silica glasses, evaluated in terms of visual color, spectral transmittance and chromaticity coordinates.

[0034] Other articles that disclose the importance of the balance between ferrous and ferric oxides in glass include: N.E. Densem, The equilibrium between ferrous and ferric oxides in glass, Journal of the Society of Glass Technology, Glasgow, England, May 1937, pp. 374-389; J.C. Hostetter and H.S. Roberts, "Note on the dissociation of ferrous oxide dissolved in glass and its relativization to the color of iron-bearing glasses", Journal of the American Ceramic Society, USA, September, 1921, pp. 927-938. Many scientific books and articles have been published on the composition of colored glass with ultraviolet and infrared radiation absorption characteristics.

[0035] In the book Color Generation and Control in Glass, Glass Science and Technology (Elsevier Science Publishing Co., Amsterdam, 1977), CR Bamford describes the principles and applications of glass coloring methods. In this book, the author argues that there are three elements that control the color of light transmitted through glass, namely the color of the incident light, the interaction of the glass with that light, and the interaction of the transmitted light with the observer's eye. The procedure requires spectral transmission data of the glass, for the corresponding glass thickness and observation angle.

[0036] Regarding titanium oxide (TiO) in silica-soda-lime glass, the most stable form of titanium in glass is tetravalent (Ti 4+ ). The trivalent form can impart coloration, however, this effect is not observed in silica-soda-lime glass. In the paper "Effects ofTi tanium Dioxide on Glass", The Glass Industry, September, 1963, pp.495-531, Beals MD describes that titanium dioxide has shown interest as a glass component. The effects produced by the use of titanium dioxide include: TiO2 greatly increases the refractive index, increases the absorption of light in the ultraviolet region, and reduces viscosity and surface tension. From the data on the use of titanium dioxide in enamels, it is observed that TiO2 increases chemical durability and acts as a flux. Generally, transparent glasses containing titanium dioxide can be found in all common glass-forming systems (borates, silicates and phosphates). The various glass-forming regions of the systems containing titanium dioxide are not concentrated together because the organization discussed is more based on the properties of the glasses containing titanium dioxide rather than their own composition. On the other hand, the addition of selenium to silica-soda-lime glass can produce pink coloration, which is due to the presence of atomic selenium. Selenium is one of the most widely used physical bleaching agents for glass, wherein trace iron is as the undesirable impurity in raw material, because its coloring can neutralize the ferrous ion and ferric ion present in glass.Due to being positioned at the absorption band (band similar to selenium atom) between 490nm and 500nm in visible region, the combination of iron oxide and selenium in silicon-soda-lime glass gives the reduction of reddish brown coloring and light transmittance.This band extends into the ultraviolet region, also causes the reduction of this type transmission in glass.The intensity of coloring and the final property of glass change with the concentration of iron oxide and selenium in glass.

[0037] It is well known that copper plays an important role in the production of glass, ceramics and colored pigments. For example, the coloring of Persian ceramics is recognized for the hue it imparts by copper. Of particular interest to ceramic artists is turquoise blue, especially Egyptian and Persian ultramarine (Waldemar A. Wei l; Colored Glasses, Society of Glass Technology, Great Britain, pp. 154-167, 1976).

[0038] Copper has been used in glass compositions, not only in those of the silicon-soda-lime type, but also in some others, such as those containing borosilicates. The color formed thus depends on the glass substrate, its concentration and its oxidation state.

[0039] In the case of sodium-silicon-lime base glasses, copper in the form of oxides imparts a greenish hue, in particular a turquoise blue coloration, whereas in the glass, copper can be in its monovalent state, which does not impart color. The blue-green coloration therefore depends not only on the amount of copper present, but also on the ionic balance between the cuprous state and the divalent cupric state. The maximum absorption of copper oxides is in a band centered at 780 nm, and the second weakest maximum peak is present at 450 nm, which disappears at high sodium contents (about 40% by weight) (CR Bamford, Color Generation and Control in Glass, Glass Science and Technology, Elsevier Scientific Publishing Company, pp. 48-50, Amsterdam, 1977).

[0040] The addition of copper oxide (CuO) in combination with iron oxide, cobalt oxide, selenium and titanium oxide is an alternative to obtain gray tones with low light transmittance for use in the automotive industry or in architecture, where the glass has a low illuminant light transmittance A(T LA ), direct sunlight transmittance not greater than 14% (T DS ), the transmittance of near infrared radiation is not more than 14% (T IR ), the transmittance of ultraviolet radiation is not more than 8% (T UV ), total solar energy transmittance (T TS), with a purity of no more than 50% and a dominant wavelength of 480-590 nm when having a nominal thickness of 3.85 mm. It has been confirmed that in industrial production, it is feasible to add CuO with a concentration of less than 120 ppm for a thickness of 4 mm, and it is feasible to add CuO with a concentration of less than 100 ppm for a thickness of 6 mm.

[0041] Solar control is the ability to vary the amount of transmitted or reflected solar radiation within the spectral intervals of the near ultraviolet (UV; 300-380nm), visible (VIS; 380-780nm), and infrared (IR; 780-2500nm) ranges. This can be accomplished by adding various absorber colorants to the initial mixture so that the glass has the property of absorbing both infrared (IR) and ultraviolet (UV) solar radiation, thereby reducing the amount of excess heat entering the vehicle interior caused by radiation from the sun, as well as protecting the interior from degradation by UV radiation from the sun.

[0042] It is also possible to manufacture the glass in different thicknesses, for example for use in the manufacture of laminated systems. If a higher concentration of CuO is present, during the formation process inside the float chamber, reduction processes due to the process atmosphere can occur, resulting in a reddish coloration on the glass surface which is observed by reflection. This effect is related to the residence time and the forward speed of the glass batten, which means that at lower speeds it would be necessary to reduce the CuO content in the glass or adjust the reduction conditions in the float chamber.

[0043] The present disclosure relates to a gray glass. In one aspect, the present disclosure includes: a low illumination light transmittance A (T LA ), direct sunlight transmittance not greater than 14% (T DS ), the transmittance of near infrared radiation is not more than 14% (T IR ), the transmittance of ultraviolet radiation is not more than 8% (T UV ), the total solar energy transmittance (T TS ), when it has a nominal thickness of 3.85 mm and is manufactured by a float process, has a purity of no more than 50% and a dominant wavelength of 480-590 nm.

[0044] In another aspect, the present disclosure relates to the use of copper oxide as a partial substitute for cobalt oxide (Co3O4). Its feasibility of addition to flat glass manufactured by the float process has been demonstrated to levels approaching 120 ppm without a reducing effect due to the conditions of the tin chamber. Similarly, TiO2 can be included as an additional element with iron oxide to provide a further reduction in ultraviolet radiation transmittance. In another aspect, the present disclosure relates to a method for obtaining a gray glass composition with low transmittance, the composition comprising an additional element such as carbon or sodium nitrate to adjust the oxidation-reduction state of the iron oxide.

[0045] The glasses of the present disclosure avoid the use of expensive coloring compounds such as oxides of nickel, chromium, manganese or rare earth elements, primarily erbium oxide (Er2O3).

[0046] The present disclosure also relates to a gray glass composition that can be implemented in automotive and non-automotive applications, such as in the construction industry or other applications, for example, it can be used as a substrate to be coated by a single layer or thin multilayers applied via a vacuum cathode etching process (MSVD), chemical vapor deposition (CVD) or other techniques.

[0047] A typical composition of a silica-soda-lime glass formed by the float glass process for the automotive industry is characterized by the following formula based on weight percentage relative to the total weight of the glass: 68% to 75% SiO2; 0% to 5% Al2O3; 5% to 15% CaO; 0% to 10% MgO; 10% to 18% Na2O; 0% to 5% K2O; and 0.05% to 0.3% SO3.

[0048] The glass composition of the present disclosure is based on silica-soda-lime glass, to which one or more of the following colorants are added to obtain a gray color. In one example, the composition includes: 1.8 wt% to 2.3 wt% Fe2O3, preferably about 2.0 wt% to about 2.2 wt% Fe2O3, or more preferably 2.04 to 2.12 wt% Fe2O3; 0.28 wt% to 1.2 wt% FeO; 15% to 40%, preferably 17% to 30%, more preferably 19% to 25% redox ratio; 0.030 wt% to 0.040 wt% Co3O4; 0.0020 wt% to 0.010 wt% Se; 0.00050 wt% to 0.050 wt% CuO; and 0.01 wt% to 1 wt% TiO 2。 Additional agents that may be added to the composition to adjust oxidation-reduction include 0.01 wt % to 1.0 wt % NaNO3 and 0 wt % to 0.07 wt % carbon.

[0049] One advantage of adding sodium nitrate (NaNO3) and carbon to the composition is that the oxidation state of the iron is adjusted to achieve a direct sunlight transmittance (T DS ) levels. In addition, sodium nitrate helps optimize selenium retention in the glass. The visible light transmittance (T LA ) is not more than 15%, direct sunlight transmittance (T DS ) is not more than 14%, infrared radiation transmittance (T IR ) is not more than 14%, and the UV transmittance (T UV ) is not more than 8%, the total solar energy transmittance (T TS ) is not greater than 38%, when it has a thickness of, for example, 1.4 to 6 mm, 1.6 to 5 mm and more preferably 3.85 mm, the purity is not greater than 50% and the dominant wavelength is 480-590 nm. The glass of the present disclosure avoids the use of coloring compounds such as oxides of nickel, chromium, manganese or rare earth elements, mainly erbium oxide (Er2O3).

[0050] The present disclosure is further described in the following numbered clauses:

[0051] Item 1. A gray glass having low light transmittance formed from a composition comprising a colorant: 1.8 to 2.3 wt% Fe2O3; 0.28 to 1.2 wt% FeO; 0.030 to 0.040 wt% Co3O4; 0.0020 to 0.010 wt% Se; 0.00050 to 0.050 wt% CuO; and 0.01 to 1 wt% TiO2, wherein the glass has a visible light transmittance (T LA ), less than 14% direct sunlight transmittance (T DS ), less than 14% infrared radiation transmittance (T IR ), less than 8% UV transmittance (T UV ), and a total solar energy transmittance (T TS ).

[0052] Item 2. The glass according to Item 1, further comprising a redox ratio of 15 to 40%.

[0053] Clause 3. Glass according to clause 1 or 2, which has an excitation purity of not more than 50% at a thickness of 3.85 mm at a wavelength of 480 nm to 590 nm.

[0054] Item 4. A glass according to any of Items 1-3, wherein the glass composition further comprises: 68 wt% to 75 wt% SiO2; up to 5 wt% Al2O3; 5 wt% to 15 wt% CaO; up to 10 wt% MgO; 10 wt% to 18 wt% Na2O; up to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3.

[0055] Clause 5. The glass according to any one of Clauses 1 to 4, wherein the colorant further comprises 0.01 wt % to 1.0 wt % NaNO 3 .

[0056] Clause 6. The glass according to any of Clauses 1-5, wherein the glass further comprises up to 0.07 wt % carbon.

[0057] Clause 7. A glass sheet comprising the glass according to any one of Clauses 1 to 6.

[0058] Clause 8. A glass sheet according to clause 7, comprising a glass sheet having a D 65 Illumination, 10° observer and including specular component measured with the following color CIELAB values: L ranging from 46 to 15 * Value; a range from -10 to 5 * values; and b ranging from -5.0 to 15 * value.

[0059] Clause 9. The glass sheet according to clause 7 or 8, which has an excitation purity of not more than 50% at a thickness of 3.85 mm.

[0060] Clause 10. The glass sheet according to any one of Clauses 7-9, wherein the dominant wavelength is from 480 nm to 590 nm.

[0061] Clause 11. A glass sheet according to any one of Clauses 7-10, formed by a float process.

[0062] Item 12. A method for making gray glass with low light transmittance using a conventional float non-vacuum glass system, the method comprising: melting a glass batch to provide a pool of molten glass; flowing the pool of molten glass onto a molten tin bath; moving the molten glass on the surface of the molten tin bath while controllably cooling the molten glass and applying force to the molten glass to provide glass of a desired thickness; and removing the glass from the molten tin bath; wherein the glass comprises: 1.8 wt % to 2.3 wt % Fe2O3; 0.28 wt % to 1.2 wt % FeO; 0.030 wt % to 0.040 wt % Co3O4; 0.0020 wt % to 0.010 wt % Se; 0.00050 wt % to 0.050 wt % CuO; and 0.01 wt % to 1 wt % TiO2, wherein the glass has a visible light transmittance (T LA ), less than 14% direct sunlight transmittance (T DS ), less than 14% infrared radiation transmittance (T IR ), less than 8% UV transmittance (T UV ), and a total solar energy transmittance (T TS ).

[0063] Clause 13. The method of Clause 12, wherein the glass comprises a redox ratio of 15 to 40%.

[0064] Clause 14. The method of clause 12 or 13, wherein the glass has an excitation purity of no more than 50% at a thickness of 3.85 mm at a wavelength of 480-590 nm.

[0065] Item 15. A method according to any one of Items 12-14, wherein the glass further comprises: 68 wt% to 75 wt% SiO2; 0 wt% to 5 wt% Al2O3; 5 wt% to 15 wt% CaO; 0 wt% to 10 wt% MgO; 10 wt% to 18 wt% Na2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3.

[0066] Clause 16. The method of any of Clauses 12-15, wherein the glass further comprises 0.01 wt % to 1.0 wt % NaNO 3 .

[0067] Clause 17. The method of any of Clauses 12-16, wherein the dominant wavelength of the glass is 480 nm to 590 nm.

[0068] Item 18. A glass comprising a colorant, the colorant comprising: 1.8 wt% to 2.3 wt% Fe2O3; 0.28 wt% to 1.2 wt% FeO; 0.030 wt% to 0.040 wt% Co3O4; 0.0020 wt% to 0.010 wt% Se; 0.00050 wt% to 0.050 wt% CuO; 0.01 wt% to 1 wt% TiO2; and a redox ratio of 15 to 40% (based on the total weight of the glass).

[0069] Clause 19. The glass according to clause 18, further comprising a visible light transmittance (T LA ).

[0070] Clause 20. The glass according to clause 18 or 19, further comprising a direct solar transmittance (T DS ).

[0071] Clause 21. The glass according to any one of clauses 18-20, further comprising an infrared radiation transmittance (T IR ).

[0072] Clause 22. The glass according to any one of clauses 18-21, further comprising an ultraviolet light transmittance (T UV ), and a total solar energy transmittance (T TS ).

[0073] Item 23. The glass according to any of Items 18-22, further comprising: 68 wt% to 75 wt% SiO2; 0 wt% to 5 wt% Al2O3; 5 wt% to 15 wt% CaO; 0 wt% to 10 wt% MgO; 10 wt% to 18 wt% Na2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3.

[0074] Item 24. The glass according to any one of Items 18-23, wherein the amount of Fe2O3 is 2.0 wt% to 2.2 wt%.

[0075] Item 25. The glass according to any one of Items 18-23, wherein the amount of Fe2O3 is 2.04 wt% to 2.12 wt%.

[0076] Example

[0077] The following examples show the following physical properties: Illuminant A light transmittance (T LA ), direct solar transmittance (T DS ), near infrared radiation transmittance (T IR), UV transmittance (T UV ), total solar transmittance (T TS ). For glass with a value of 3.85, the color transmission (L * 、a * and b * )(color transmi ss ion), color purity and dominant wavelength (l).

[0078] Table 1 and Table 2

[0079] Tables 1 and 2 (Examples 1 to 14) show the experimental results of the disclosed compositions having combinations of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO). In addition, they contained 0.66% sodium nitrate (NaNO3) as an oxidant in the mixture, and no carbon was added.

[0080] Table 1

[0081] Table 2

[0082] Table 3

[0083] Table 3 (Examples 15 to 18) shows the experimental results of the disclosed compositions with combinations of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide and titanium oxide (TiO). In addition, 0.16% sodium nitrate (NaNOs) and 0.04% carbon (coke type) were incorporated into the mixture.

[0084] Table 4

[0085] Table 5

[0086] Tables 4 and 5 (Examples 19 to 31) show the experimental results of the disclosed compositions having a combination of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO). Also, they contained 0.16% sodium nitrate (NaNO3) and 0.02% carbon in the mixture.

[0087] Table 6

[0088] Table 6 (Examples 32 to 34) shows the experimental results of the disclosed compositions having a combination of iron oxide (Fe2O3), cobalt oxide or cobalt tetraoxide (CoO or Co3O4), selenium (Se), oxycopper and titanium oxide (TiO2). In addition, they contain 0.16% sodium nitrate (NaNO3) and 0.030% carbon. The main purpose of adding sodium nitrate (NaNO3) and carbon to the composition is to adjust the oxidation state of iron to achieve the optimal level of direct sunlight transmittance (T DS ). In addition, sodium nitrate helps optimize selenium retention in the glass. Color and privacy are adjusted by optimizing the dye percentages described in this disclosure.

[0089] Other embodiments of the present disclosure include the following contents shown in Table 7.

[0090] Table 7

[0091] Additional experimental examples are shown below in Table 8.

[0092] Table 8

[0093] The redox ratios of the above examples ranged from 0.2 to 0.3, with an average of 0.25. The physical properties of the resulting glass were evaluated according to internationally recognized standards. The tristimulus colorimeter values ​​(x, y, and z) that have been adopted by the International Commission on Illumination (CIE) derive specifications for color determination, such as dominant wavelength and excitation purity, as a standard direct result of experiments involving many observers. These specifications can be determined by calculating the tristimulus coefficients x, y, and z corresponding to the tristimulus colorimeter values ​​for red, green, and blue, respectively. The tristimulus values ​​are plotted on a chromaticity diagram and compared with the coordinates of illuminant D65, which is considered a lighting standard. This comparison provides information to determine the color excitation purity and its dominant wavelength. The dominant wavelength defines the wavelength of the color, and its values ​​are in the visible range, from 380nm to 780nm, while for excitation purity, the lower its value, the closer it is to a neutral color.

[0094] UV transmittance (T UV ) calculations are adjusted to the range of solar UV radiation and are therefore evaluated in 10 nm intervals in the range of 300 nm to 400 nm as indicated in ISO standard DIS13837.

[0095] For the evaluation of light transmittance, an illuminant "A" (T LA), integrated logarithmically at 10 nm intervals over the wavelength range of 400 to 800 nm. Color transmission (L * , a * and b * ).

[0096] According to ISO / DIS13837 standard, direct sunlight transmittance (T) was evaluated in the range of 300 to 2500 nm at intervals of 5, 10 and 50 nm. DS ) value.

[0097] In the infrared transmittance (T IR ), considering the range included in the radiation of the solar spectrum, having a range of 800 to 2500 nm, with an interval of 50 nm, using the values ​​of the ISO / DIS13837 standard.

[0098] According to ISO / DIS13837, the total solar transmittance (T) was evaluated in the range of 300 to 2500 nm, considering a wind speed of 4 m / s (steady). TS ).

[0099] The neutral gray glass of the present disclosure can be manufactured by float glass process with a thickness of 1.4 mm to 6 mm. However, the present disclosure is not limited to this thickness range and can be processed in a tempered form, in a glazing system, a double-layer stacking process, or as a substrate covered by one or more layers.

[0100] The glass has the following properties: the transmittance of light from the illuminant A (T LA ) is not more than 15%, direct sunlight transmittance (T DS ) is not more than 14%, near infrared radiation (T IR ) is not more than 14%, and the UV transmittance (T UV ) is not more than 8%, the total solar energy transmittance (T TS ) is not more than 38%, and the purity is not more than 50%.

[0101] Those skilled in the art will readily appreciate that the disclosure may be modified without departing from the concepts disclosed in the foregoing description. Therefore, the specific examples described in detail herein are merely illustrative and do not limit the scope of the disclosure, and the appended claims and any and all equivalents thereof will give the full breadth of the scope of the disclosure.

Claims

1. Gray glass with low light transmittance, which contains colorants: 2.04 to 2.12 wt% Fe2O3; 0.28 wt % to 1.2 wt % FeO; 0.030 wt % to 0.040 wt % Co3O4; 0.0020 wt % to 0.010 wt % Se; 0.00050 wt % to 0.050 wt % CuO; and 0.01 wt% to 1 wt% TiO2.

2. The glass according to claim 1, comprising a visible light transmittance (T LA ).

3. The glass according to claim 1, comprising a direct solar transmittance (T DS ).

4. The glass according to claim 1, comprising an infrared radiation transmittance (T IR ).

5. The glass according to claim 1, comprising an ultraviolet light transmittance (T UV ), and a total solar energy transmittance (T TS ).

6. The glass according to claim 1, further comprising a redox ratio of 15-40%.

7. The glass according to claim 1, which has an excitation purity of not more than 50% at a thickness of 3.85 mm at a wavelength of 480-590 nm.

8. The glass according to claim 1, further comprising: 68 to 75 wt. % SiO2; 0 to 5 wt% Al2O3; 5 to 15 wt% CaO; 0 to 10 wt% MgO; 0 to 18 wt% Na2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3.

9. The glass of claim 1, wherein the colorant further comprises 0.01 wt% to 1.0 wt% NaNO3.

10. The glass of claim 1, wherein the colorant further comprises 0 wt% to 0.07 wt% carbon.

11. The glass according to claim 1, wherein the amount of Fe2O3 is 2.0 wt% to 2.2 wt%.

12. The glass according to claim 1, wherein the amount of Fe2O3 is 2.04 wt% to 2.12 wt%.

13. The glass of claim 1 comprising the following color CIELAB values ​​measured using an integrating sphere with D65 illumination, 10° observer, and including specular components: L range from 46 to 15 * value; a range from -10 to 5 * value; and b ranges from -5.0 to 15 * value.

14. A method for manufacturing gray glass with low light transmittance using a conventional float non-vacuum glass system, the method comprising: melting a glass batch to provide a pool of molten glass; causing a pool of molten glass to flow onto a bath of molten tin; moving molten glass over a surface of a molten tin bath while controllably cooling and applying forces to the molten glass to provide glass of a desired thickness; and removing the glass from the molten tin bath; The glass colorant comprises: 1.8 to 2.3 wt% Fe2O3; 0.28 wt % to 1.2 wt % FeO; 0.030 wt % to 0.040 wt % Co3O4; 0.0020 wt % to 0.010 wt % Se; 0.00050 wt % to 0.050 wt % CuO; and 0.01 wt% to 1 wt% TiO2.

15. The method of claim 14, wherein the glass comprises a redox ratio of 15 to 40%.

16. The method of claim 14, wherein the glass further comprises: 68 to 75 wt. % SiO2; 0 to 5 wt% Al2O3; 5 to 15 wt% CaO; 0 to 10 wt% MgO; 0 to 18 wt% Na2O; 0 wt% to 5 wt% K2O; and 0.05 wt% to 0.3 wt% SO3.

17. The method of claim 14, wherein the glass further comprises 0.01 wt% to 1.0 wt% NaNO3.

18. The method of claim 14, wherein the dominant wavelength of the glass is 480 nm to 590 nm.

Citation Information

Patent Citations

  • Colored glass compositions and glazings produced therewith

    US5352640A

  • Composition for colored glass intended for the manufacture of glazing panes

    US5545596A

  • Ultraviolet / infrared absorbent low transmittance glass

    US7393802B2

  • Grey glass composition

    US7622410B2

  • Low-luminous-transmittance glass

    US7754632B2